EFFECTS OF ISOTRETINOIN ON PLATELET COUNT AND MEAN PLATELET VOLUME DURING TREATMENT OF ACNE VULGARIS - SAEED, M; RAFIQUE, S; ULLAH, MA; DAWOOD, N; MALIK, LM; RASHID, T (Biological and Clinical Sciences Research Journal, 2023)
The most effective systemic therapy for acne is Isotretinoin. However, Isotretinoin has many side effects, including known side effects like dryness, palmoplantar exfoliation, rash, teratogenicity, raised intraocular pressure, and deranged liver functions and lipid profile. Its lesser-known side effects include its effects on platelet count and mean platelet volume (M.P.V.). This Quasi-experimental case series was conducted to observe the change in platelet count and mean platelet volume in patients taking Isotretinoin for acne vulgaris, attending the dermatology outpatient department at Jinnah Hospital Lahore from May 10th 2016 to November 9th 2016. After ethical committee approval and informed consent, subjects of acne vulgaris with an indication for Isotretinoin were included in the study from O.P.D. Relevant demographic and clinical details were recorded in a standardized predesigned proforma. Citrated blood samples were taken under aseptic conditions. Baseline platelet counts and mean platelet volume were determined using an auto-analyzer in the pathology laboratory of Jinnah hospital Lahore. All the patients were advised to take daily Isotretinoin at a dose of 0.5 mg/kg for 12 weeks. Platelet counts and mean platelet volume were again measured after twelve weeks after the start of treatment. A total of 100 patients completed the study. The age of the patients ranged from 18 to 60 years with a mean + sd age of 27.26+5.88 years. Out of these 41%(n=41) were male and 59%(n=59) were females. The severity of acne was measured using Global Acne Grading System (G.A.G.S.). It was recorded that 62%(n=62) had moderate, 22%(n=22) had severe while 16%(n=16) had very severe acne vulgaris. The mean pre-treatment platelet count was 271273+9139 c/µL, while 259192+11717 c/µL was post-treatment. The mean difference was 12080+8140 c/µL, and the p-value was 0.001. The mean platelet volume was 10.63+1.01 fl as pre-treatment and 9.77+1.01 fl as post-treatment. The mean difference was 0.85+0.04 fl, and the p value was 0.001. We concluded that Isotretinoin decreases platelet count and means platelet volume in patients receiving isotretinoin treatment for acne vulgaris.